Discovery of an Association Between Influenza Infection Rates and the Incidences of Craniosynostosis in the United States: A Potentially Modifiable Risk Factor. (October 2020) - Mabes, Erika Simmerman; Moraczewski, Jason; Chishom, Taylor; Dymanus, Kyle; Linder, Daniel; Yu, Jack C.
Objective: Maternal immune activation secondary to influenza infection during critical periods of fetal development is a significant risk factor for neuropsychiatric and neurodevelopmental disorders. The association between influenza and craniosynostosis is not well documented. We investigate the association between the incidence of influenza infection and incidence of craniosynostosis in the United States.Materials and Methods: Retrospective population-based observational study spanning using the National Inpatient Sample Database, the United States Center for Disease Control and Prevention FluView databases, including infants born with craniosynostosis in the United States from 2004 to 2013 and monthly influenza incidence in the United States from 2003 to 2013. Mixed-effects logistic regression tested the association between 2 variables: national influenza incidences and rate of craniosynostosis. Odds ratios were calculated for the occurrence of craniosynostosis in relation to previous months' flu incidence. E -values were calculated to evaluate unmeasured confounders.Results: Retrospective analysis performed on 45 356 newborns with craniosynostosis. Mixed-effects logistic regression revealed for each additional influenza case per 1000 people, the odds of craniosynostosis event occurring 6 months later increased by 3.4 (adjusted P  = .009, OR = 3.444, CI = 1.756-6.754). For each additional influenza case per 1000 people, the odds of craniosynostosis event occurring 7 and 2 months later decreased by 3.8 and 6.1, respectively (OR = 0.262 and 0.165; adjusted P value = .007 and <.001). E-value for the association between influenza and craniosynostosis incidence 6 months later was 6.35. The E -values for the association between influenza and craniosynostosis incidences 7 months and 2 months later were 7.1 and 11.6.Conclusion: There is an increased risk for craniosynostosis with influenza occurring in third month of pregnancy. There are protective effects against craniosynostosis with influenza occurring in second and seventh months of pregnancy. To our knowledge, this is the first study demonstrating an association between the rate of influenza and craniosynostosis, suggesting a potentially important connection, though not necessarily causality, between maternal immune activation and craniosynostosis.